Near-Infrared Photoactivatable Immunomodulatory Nanoparticles for Combinational Immunotherapy of Cancer - Yu, Ningyue; Ding, Mengbin; Li, Jingchao (Frontiers in Chemistry, 2021)
As a promising treatment option for cancer, immunotherapy can eliminate local and distant metastatic tumors and even prevent recurrence through boosting the body’s immune system. However, immunotherapy often encounters the issues of limited therapeutic efficacy and severe immune-related adverse events in clinical practices, which should be mainly due to the non-specific accumulations of immunotherapeutic agents. Activatable immunomodulatory agents that are responsive to endogenous stimuli in tumor microenvironment can afford controlled immunotherapeutic actions, while they still face certain extent of off-target activation. Since light has the advantages of noninvasiveness, simple controllability and high spatio-temporal selectivity, therapeutic agents that can be activated by light, particularly near-infrared (NIR) light with minimal phototoxicity and strong tissue penetrating ability have been programmed for cancer treatment. In this mini review, we summarize the recent progress of NIR photoactivatable immunomodulatory nanoparticles for combinational cancer immunotherapy. The rational designs, constructions and working mechanisms of NIR photoactivatable agents are first briefly introduced. The uses of immunomodulatory nanoparticles with controlled immunotherapeutic actions upon NIR photoactivation for photothermal and photodynamic combinational immunotherapy of cancer are then summarized. A conclusion and discussion of the existing challenges and further perspectives for the development and clinical translation of NIR photoactivatable immunomodulatory nanoparticles are finally given.